Analysis of the quality of Arabic-speaking skills test for madrasah aliyah students in Makassar - Hamidah, Nisriani Fatin; Syahrul, Syahrul; Ishak, Suryadi; Asripan, Andi; Vivekanantharasa, Raveenthiran (Universitas Sarjanawiyata Tamansiswa, 2025)
This study analyzed the validity and reliability of the Arabic-speaking skills test for Madrasah Aliyah students in Makassar. Speaking skills were essential in Arabic language learning, especially in the context of Islamic education in Indonesia. This study aimed to determine whether the test used had adequate construct validity and reliability in assessing students’ speaking skills. Construct validity was examined through principal component analysis, while internal consistency reliability was measured using Cronbach’s alpha and McDonald’s omega. Data were obtained from a speaking test administered to student samples and analyzed with statistical software. The results indicated that several test items were problematic and required revision. The low Cronbach’s alpha value highlighted issues in inter-item correlations, affecting the overall reliability of the test. The study concludes that the instrument needs refinement to improve measurement accuracy and emphasizes the importance of ongoing evaluation in the development of Arabic speaking assessment tools.